Do coador de pano à cápsula: as mudanças nas práticas de consumo de café no Brasil nos últimos 50 anos - Teixeira, Ana Paula Pydd (Universidade do Vale do Rio dos Sinos, 2014)
Habits and daily practices were not, until recently, much valued in consumer research. In general, the work turned to the special and extraordinary conditions of consumption and symbolic analysis. The importance of the mundane aspects of research lies in the reason, as obvious as true , that it is in everyday life and in trivial situations occurring most of our consumer elections. Coffee, in Brazil, is item considered the junction minimum and mandatory food for an adult citizen, being the product most consumed by Brazilians. The observation of coffee consumption allows us to understand how a mundane product can be of special features and how practices modify and rearrange over time. This study used a micro analysis at everyday consumption practices through in-depth interviews in conjunction with the analysis of macro social and structural developments made possible through a research of papers. The goal was to capture important milestones on which to judge the evolution of practices and their consequences through the use of the Practice Theory. Practice Theory has its origin among theorists such as Bourdieu (1983) and Giddens (1984), who analyze the existence of social structures that interfere in the regulation of human routines and practices. We sought, beyond the understanding of practices as the junction of three elements: actions, objects and meanings (ARSEL e BEAN, 2013) as well as the understanding of these “entities in themselves." (SCHATZKI et al., 2001). Everyday practices often have different rhythms, which often do not follow chronological patterns. Structural changes such as the entrance of women into the labor market may prove important for the relocation of the practices and modifying its temporal texture. The objects have failed to capture the earned academic interest, despite its importance for patterns of social reproduction. (LATOUR, 2012; SHOVE, 2007). Artifacts such as cloth strainer and coffeemakers are relevant for the development, maintenance and relocation of consumption practices.
Keywords: Everyday; Consumption; Practice; Secular; Cotidiano; Consumo; Prática; Mundano; ACCNPQ::Ciências Sociais Aplicadas::Administração